Principles of Spread-Spectrum Communication Systems - Torrieri, Don (Springer International Publishing, 2018)
This thoroughly revised textbook provides the fundamentals of spread-spectrum systems with a continued emphasis on theoretical principles. The revision includes new sections and appendices on characteristic functions and LaPlace transforms, orthonormal expansions of functions, the SNR wall in detection, multiple-input multiple-output systems, multicode and multirate systems, interference cancelers, complementary codes, chaos and ultrawideband systems, and the normalized LMS algorithm. As with previous editions, the author presents topics in a practical way that is of interest to both researchers and system designers. He includes updated problems at the end of each chapter, which are intended to assist readers in consolidating their knowledge and to provide practice in analytical techniques. In addition to the new and revised material, the author adds 50 new pages to make the book more accessible to graduate students in electrical engineering. .